Rheumatoid arthritis: effects of a new agent (ICI 55 897) on serum acute phase proteins and the erythrocyte sedimentation rate. Issue 1 (February 1980) - McConkey, B; Amos, R S; Billingham, M E; Constable, T J; Crockson, R A; Crockson, A P; Forster, P J
Abstract : Thirty-four patients with rheumatoid arthritis (RA) were treated with a new agent (ICI 55 897) in addition to basic therapy with nonsteroid anti-inflammatory drugs. Five patients had the drug for less than 28 days; the remaining 29 were observed for periods up to a year. At 140 days, when all but 2 patients were in the study, there had been statistically significant improvement in clinical score, serum C-reactive protein, erythrocyte sedimentation rate, and plasma fibrinogen. Thereafter results continued to improve but were biased because some patients had stopped taking the drug. The final conclusion was that 17 patients had improved with 1 late relapse, and 15 had not responded. Adverse effects were trivial except in 2 instances: one patient had a transient unexplained rise in blood urea, another had a haematemesis. Neither effect could be attributed with certainty to the drug. ICI 55 897 has no intrinsic analgesic or anti-inflammatory properties. We suggest the findings of this study indicate that this agent, with low toxicity and the ability to lower acute-phase protein levels, may be an alternative to gold or penicillamine in the treatment of RA.